Stability and Bifurcation Analysis of a Nonlinear Discrete Logistic Model with Delay - Daiyong Wu; Hai Zhang; Jinde Cao; Tasawar Hayat (Discrete Dynamics in Nature and Society)
We consider a nonlinear discrete logistic model with delay. The characteristic equation of the linearized system at the positive equilibrium is a polynomial equation involving high order terms. We obtain the conditions ensuring the asymptotic stability of the positive equilibrium and the existence of Neimark-Sacker bifurcation, with respect to the parameter of the model. Based on the bifurcation theory, we discuss Neimark-Sacker bifurcation direction and the stability of bifurcated solutions. Finally, some numerical simulations are performed to illustrate the theoretical results.